Comparative Study on the Dahi-prepared from Whole Milk, Skim Milk, Reconstituted Milk and Recombined Milk - Uddin, MR; Mazed, MA; Islam, MS; Hassan, N; Khan, MAS (Journal of Environmental Science and Natural Resources, 2015)
Dahi was prepared from whole milk, skim milk, reconstituted and combined milk by adding 12% sugar to each type and then these milks were boiled to reduce the volume by 30%. After adding 3% starter culture all these dahi mix were incubat ed at 40°C for 4-5 hours. Then all the dahi samples were kept in the refrigerator at 4°C for at least 2 hours. All these types of dahi were judged by a panel of expert judges to determine the physical qualities. Chemical and microbiological tests were also car ried out to determine the composition and qualities. Whole milk dahi was the best for overall acceptabili ty followed by skim milk dahi but other two types were somewhat less acceptable. There was a significant difference (P<0.01) among the overall scores obtained. There were a significant difference (P<0.01) in percent acidity, for all the samples % DM, % fat, % protein and % ash showed a non significant difference. For all the chemical qualities, dahi from whole milk ranked the highest followed by others types. Among the microbial qualities, total viable counts were higher in all the sample, though there was a significant difference (P<0.05). Yeast and mold counts differed significantly (P<0.01), although the counts were lower. Although, dahi prepared from reconstituted and recombined milk were not as good as that from whole milk, there is a great prospect to improve the qualities. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22076 J. Environ. Sci. & Natural Resources, 6(1): 261-266 2013